The Effect of Using Guided Questions Technique on Students’ Ability in Writing Personal Letter at MAN 2 Kuantan Singingi - masitha rahma (Indonesian Journal of Integrated English Language Teaching, 2021)
The objectives of this research were to know the average score of students’ ability in writing personal letter before and after being taught by using Guided Questions Technique and to examine whether there is significant effect of Guided Questions Technique on students’ ability in writing personal letter. This research was a pre-experimental design in the form of one group pre-test and post-test design on quantitative approach. The population of the research was the students of the eleventh grade at MAN 2 Kuantan Singingi consisting of 4 classes (XI IPA 1, XI IPA 2, XI IPS 1, and XI IPS 2). By having cluster sampling, it has been selected 20 students from XI IPS 1 out of 105 students on population. To collect the data, the researcher used writing test to know the students’ ability in writing personal letter. The data were analyzed by non-parametric test since the assumption of normally distributed data was not markedly violated. However, the data were interpreted by using Wilcoxon on the SPSS version 23.0 program. The result of the data analyzed showed that the mean score of the students after being taught by using Guided Questions Technique (82.81) was higher than before being taught by using Guided Questions Technique (68.59). In conclusion, the use Guided Questions Technique shows a significant effect on the students’ ability in writing personal letter at MAN 2 Kuantan Singingi.